Giving insights into an ICF training: evaluation of an in-person interactive ICF training in Germany - Kirschneck, Michaela; Kus, Sandra; Coenen, Michaela (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe World Health Organization (WHO) adopted the International Classification of Functioning, Disability and Health (ICF) in 2001. The classification provides a framework for the standardised description of functioning and disability using health and health-related domains. The implementation of the ICF is diverse and has a wide range of applications. A thorough understanding of the ICF classification is essential for successful implementation. We developed and delivered an in-person interactive ICF training to facilitate the implementation of the ICF in Germany. The aim of this paper is to present the evaluation of this in-person interactive ICF training.MethodsThe evaluation was conducted with questionnaires assessing the organisation of the workshops and the knowledge gained during the training using Likert scaled questions. Open-ended questions were used to gather feedback on the further development of the ICF training. Data were analysed descriptively using absolute and relative frequencies. Open-ended questions were analysed qualitatively.ResultsBetween 2017 and mid-2020, a team of trainers at the Chair of Public Health and Health Services Research (IBE) at LMU Munich organised 12 in-person interactive ICF trainings with a total of 191 participants. In total 151 participants filled in the questionnaires (response rate: 79.1%). The participants` professional backgrounds were primarily in the social sector (n = 76; 50.3%), clinical sector (n = 36; 23.8%), and administrative sector (n = 31; 20.5%). 42.4% of the participants strongly agreed that the content was relevant to their work, while an additional 51.0% almost agreed. According to this evaluation, 82.1% of the participants would recommend the training to others.DiscussionA number of constructive suggestions and proposals were made for the further development of the training programme. These mainly related to the content of the training, such as the themes of children and youth and integration assistance.